Determinan Nilai Perusahaan di Indonesia: Kajian Empiris Pada Perusahaan Sub Sektor Makanan - Utami, Fadillah Rabbiatul; Kusmayadi , Iwan (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This empirical study is an explanatory-research that examines and discusses firm value and reveals the influencing factors, namely capital structure, firm size, and profitability. The research object is companies listed on the Indonesia Stock Exchange (IDX), using a sample of 17 companies in the food and beverage sub-sector through purposive sampling. The data for this study consist of annual financial report documentation sourced from secondary data that have been fully published from 2018 to 2022 on the official website of the Indonesia Stock Exchange (www.idx.co.id). Based on panel data regression analysis through model testing using Chow test and Hausman test, the most appropriate model used in this research is the Fixed Effect Model (FEM). This research proves that firm size and profitability variables have a significant influence on firm value, while the capital structure (DER) does not have a significant.